Effect Of Corn Straw Fermentation Time (Zea mays L) Using Aspergillus niger On Nutritional Concept - Dicky Kurniawan; Sri Sukaryani; Engkus Ainul Yakin (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
This study aims to determine the optimal time of fermentation using Aspergillus niger on the pH value, dissolved protein and levels of ash content corn straw. The design used was a Completely Randomized Design (CRD) of unidirectional pattern consisting of 4 treatments repeated 3 times namely P0 : corn straw fermented with Aspergillus niger for 0 days, P1 : corn straw fermented with Aspergillus niger for 4 days, P2 : fermented corn straw with Aspergillus niger for 8 days, P3 : corn straw fermented with Aspergillus niger for 12 days. The parameters observed were pH value, dissolved protein and ash content. The results showed that corn straw fermented with Aspergillus niger had a very significant effect (P <0.01) on the pH value, dissolved protein content and ash content. Corn straw fermentation using Aspergillus niger for 0 - 12 days has a very significant effect on the pH value, dissolved protein content and ash content (P <0.01). The average pH value of the treatment P0: 5,00, P1: 6,13, P2: 6,51, P3: 6,84 The average value of dissolved protein content in the treatment P0: 27,09%, P1: 33,31%, P2: 24,14%, P3: 25,51%. The average value of ash content in the P0: 8,91%, P1: 11,34%, P2: 10,06%, P3: 9,22%, As well as the optimal time achieved in fermentation for 4 days for dissolved protein content and ash content. Keywords: Corn straw, Aspergillus niger, Fermentation, pH value, Dissolved protein content, Ash content